Cartography and Code: Incorporating Automation in the Exploration of Medieval Mappaemundi. Issue 1 (20th December 2019) - Wacha, Heather; Levernier, Jacob
Abstract : The study of medieval mappaemundi has traditionally relied on comparative analysis as one of the methods to examine and identify possible centres of map production, common sources and conceptions of space and place, as well as possible social, institutional, ideological, and economic connections between maps. The comparison of place names between medieval mappaemundi is one of the ways scholars can compare toponyms across maps, but this has, until now, been conducted by hand, usually on a case by case study. This paper introduces a new digital tool called veccompare, designed to facilitate an in-depth study of the relationships between mappaemundi vis à vis their textual content. As a case study, veccompare has been used for the comparison of two Psalter maps. Veccompare's output report and visualization of data has led to a better understanding of the Psalter maps' close physical proximity, namely on the same folio in the same manuscript. It may be pursuant not to a direct, one-to-one, model-derivative type of relationship between the maps, but rather to an indirect relationship stemming from a common textual source used by both mapmakers.